Analysis of particle migration and agglomeration in paste mixing based on discrete element method. (17th October 2022) - Li, Xue; Li, Cuiping; Ruan, Zhuen; Yan, Bingheng; Hou, Hezi; Chen, Long
Highlights: A novel method of paste flow behavior during mixing process is proposed. The parameters of paste are calibrated based on the Hertz-Mindlin with JKR model. The effect of particle dispersion is influenced by agglomeration. The interactions result in changes in the mesostructure of paste. Abstract: Mixing plays an important role in paste filling technology, but there exists poor flowability of paste and low strength of cement paste backfill in production, which is due to the fact that the material is not evenly dispersed in the mixing process. In this paper, the flow behavior of paste was simulated by the discrete element method (DEM) during mixing process, and the parameters of the particle contact model were calibrated by rheological tests and slump tests. It can be seen that there was a good correlation between the flow behavior and the simulation. The surface energy was set to 4.8 J/m 3, which could reflect the interparticle force. It was found that the particle agglomeration affected the particle motion, while the van der Waals and electrostatic forces influenced the particle interactions under shearing. The average coordination number of particles showed an increasing trend at t  = 45 s, as did the contact force between particles. This study provides new insight into the mechanism of mesostructure evolution of the paste under strong shearing and lays the foundation for quantifying the effect of inter-particle mechanical interaction on the fluidity of the paste.